Design improvement of a versatile ducted-fan UAV / Adnan Maqsood and Tiauw Hiong Go - Maqsood, Adnan; Tiauw, Hiong Go (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2012)
The paper discusses the aerodynamic design improvement of a ducted fan unmanned Aerial vehicle (UAV). The UAV is capable of take-off vertically, hover and transition to cruise and is equipped with wing. the aerodynamics of the UAV is estimated through wind-tunnel experiments. The design improvement is carried out for the two phases of mission profile: hover and cruise.